THE CALCULATION OF EVAPORATION LOSS IN TANK Y AND TANK Z AT PT X PRABUMULIH - Sefilra Andalucia (Journal of Earth Energy Engineering, 2023)
Calculation Evaporation Loss (Fixed Roof Tank) on Tank Y and Tank Z in SA Field, PT X Prabumulih. The calculation of evaporation loss consists of breathing loss and working loss. By calculating breathing loss and working loss, it can be known the losses that occur in a tank. The most significant parameters in influencing breathing loss are temperature and ullage tanks, while parameters that greatly affect working loss are true vapor pressure and trhoughput. After calculating, the total losses that occurred in Tank Y and Tank Z were obtained as much as 3.46 Bbl / day or 1,261.41 Bbl / year, if assumed with the Indonesian Crude Price (ICP) price of crude oil per barrel is currently US $ 117.62 then the loss incurred in Tank Y and Tank Z is Rp. 2,209,762,045 / year.